Transvaginal ultrasound evaluation of the ureter - Juan Ramón Pérez Vidal; Carmen Llanos Llanos; Inmaculada Gómez Carrascosa; María Orenes Moreno; Pilar Marín Sánchez (Korean Society of Obstetrics and Gynecology, 2022)
Objective In this video, we present our technique for ureter assessment during pelvic ultrasound examination. Methods We used a general electric Voluson E10 (General electric, Wauwatosa, WI, USA) to perform transvaginal ultrasonography. These images were shared after thorough counselling, and obtaining informed consent from the patient. This video was edited using FinalCut ProX® (Apple Inc, Cupertino, CA, USA). Results We systematized this routine after assessing the cervix, uterus, and adnexa. The vaginal probe was slightly removed to focus on the urethra. Next, we approached the hand on the contralateral thigh to the ureter. At this point, the probe was directed to the lateral pelvic wall where the ureteric orifice was found. Then, we raised our hands and perform an internal rotation movement to ascend the ureteral segments until it is related to the iliac vessels. Conclusion The urinary tract may be involved in gynecological pathologies. Transvaginal ultrasound is an easy, reproducible, and well-tolerated examination that can be used to evaluate the ureters below the pelvic brim.